A HOUSEFUL OF POTS: APPLYING ETHNOARCHAEOLOGICAL DATA TO ESTIMATE ANNUAL CERAMIC VESSEL CONSUMPTION RATES OF CLASSIC MAYA HOUSEHOLDS. Issue 1 (9th March 2017) - Straight, Kirk Damon
Abstract: This article reviews data from the modern highland Maya area in order to develop a model of vessel discard frequencies applicable to Classic Maya contexts. Estimating the number of pots consumed by ancient households is crucial to reconstructing the organization of ceramic production and exchange in antiquity. The recent publication of in situ household assemblages from the Classic Maya center of Aguateca facilitates an analysis of household pottery use during the Late Classic period. Vessel class use-lives derived from ethnoarchaeological studies are applied to the Aguateca assemblages to estimate annual consumption rates. The simulated Aguateca discard assemblages are then compared to archaeologically recovered vessel class discard frequencies from the Classic Maya center of Tikal. The article concludes with a discussion of how and why pottery requirements for Classic Maya households differed from those of twentieth century Maya and the implications these distinctions have for interpreting consumption pattern for the Classic Maya.